Rancang Bangun Sistem Monitoring Kebisingan pada Ruangan dengan Sensor Suara GY-MAX4466 Berbasis Internet of Things (IoT) - Lia Wilani; Mardian Peslinof; Jesi Pebralia (Universitas Indraprasta PGRI Jakarta, 2023)
This research is conducted on the design of noise monitoring system in rooms using the GY-MAX4466 sound sensor based on the Internet of Things. The aim of the research is to produce a noise monitoring system that can measure in real time and has measurement characteristics. The method used consists of problem analysis, design, tool assembly, characteristic test and test result data analysis. The characteristics include accuracy, precision, and overall system test. The resulting monitoring system consists of a monitoring tool and a user interface blynk on a smartphone. The design of the monitoring system utilizes the GY-MAX4466 sound sensor to detect sound intensity level and the NodeMCU ESP8266 as a microcontroller that can exchange data via the internet network. Information on the noise level in the room can be viewed through the blynk application. The results of the test show the system has an accuracy value of 97.58 % and a precision value of 97.84%. Overall, the system has been successfully implemented. In its implementation in the Electronics, Robotics and Automation Laboratory, the system can effectively monitor noise at a distance of 2 meters.